An improved resonant wireless power transfer system with optimum coil configuration for capsule endoscopy - Basar, M.R.; Ahmad, M.Y.; Cho, J.; Ibrahim, F. (Elsevier, 2016)
Resonant wireless power transfer is a prominent method of powering a biomedical capsule endoscope, in which the high efficiency of an inductive power link and the electromagnetic safety of biological tissues are greatly important. This paper presents a complete analytical model of a resonant wireless power transfer link, where the efficiency is remarkably increased with the improved power transmission coil configuration. This configuration involves two outer coils and one middle coil. The separation and turn ratios between the outer coils and the middle coil are 0.4 times of the coil radius and 3:2, respectively. An analysis of and comparison with the existing coil configuration show that the proposed configuration relatively attains higher Q-factor, coupling coefficient, and H-field uniformity, which lead to improvement in power transfer efficiency, stability, and electromagnetic safety. The analysis is validated through experiments. With a power receiving coil of Ø11 mm × 8 mm, the proposed power transfer coil attains a minimum efficiency of around 36.6% at the worst position of the power-receiving coil. The attained efficiency was 156% higher than the efficiency of 14.62% obtained by the best of existing coil at the same level of H-field uniformity. Incorporating high permeability core, up to 200 mW of power is transferred with the proposed coil at 300 kHz in accordance with the electromagnetic safety guideline.